2002
DOI: 10.1504/ijep.2002.000678
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of street canyon concentrations on above-roof wind speed - implications for numerical modelling

Abstract: In micro-scale numerical modelling of street canyon pollution, an inverse proportionality of additional concentration (C) with wind speed (U_roof) is often assumed for cases without buoyancy, stability effects, solar radiation and traffic induced turbulence. Detailed data analyses of two comprehensive field datasets from Göttinger Straße in Hannover and Jagtvej, Copenhagen including concentration and wind field measurements in the street and above the roof are presented. A significant deviation from the 1/U_ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…For micro-scale numerical modelling 10 of street canyon air pollution, the traffic-related component of ambient pollutant concentration 11 is generally assumed to be inversely dependent on above-roof wind speed, in particular when 12 solar radiation is weak, stratification is neutral, and traffic-induced turbulence is ignored 13 (Berkowicz, 2000). The direction of the wind (cross-canyon or along canyon) is also 14 important in determining the flow and mixing processes in the street canyon and the 15 consequent pollutant concentrations (Ketzel et al, 2002). At low wind speeds traffic-16 produced turbulence and thermal effects become important.…”
Section: Introductionmentioning
confidence: 99%
“…For micro-scale numerical modelling 10 of street canyon air pollution, the traffic-related component of ambient pollutant concentration 11 is generally assumed to be inversely dependent on above-roof wind speed, in particular when 12 solar radiation is weak, stratification is neutral, and traffic-induced turbulence is ignored 13 (Berkowicz, 2000). The direction of the wind (cross-canyon or along canyon) is also 14 important in determining the flow and mixing processes in the street canyon and the 15 consequent pollutant concentrations (Ketzel et al, 2002). At low wind speeds traffic-16 produced turbulence and thermal effects become important.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was demonstrated that k-ɛ turbulence model is usually the choice (e.g. Ketzel et al, 2002) due to the convenient compromise between its computational economy, robustness and accuracy. In this investigation, proposed CFD model, based on the enhanced k-ɛ turbulence closure, was previously validated on lid-driven 2D recirculating flows (Michelsen et al, 1986) in closed 2D triangular and trapezoidal cavities with one or two moving lids (Darr et al, 1991), demonstrating accurate predictions of the fundamental flow features (SolidWorks Flow Simulation Technical Paper, 2013).…”
Section: Model Validationmentioning
confidence: 99%
“…One alternative to theoretical modelling used by other authors in the field (Ketzel et al , 1999; Kukkonen et al , 2001; Kassomenos et al , 2004), and the approach that is taken in this article, is to use existing air pollution data from a site of interest to develop a site‐specific semi‐empirical model for making predictions and understanding the local behaviour of the particular site. The model presented has deliberately been kept as simple as possible and no pollution‐specific factors influencing concentrations (such as rainfall or solar radiation) have been included.…”
Section: Motivation For the Study And The Semi‐empirical Approachmentioning
confidence: 99%
“…At the same time, pollutants are introduced into the box through advection of the background concentration. In the present model, a wind speed offset ( u o ) is included in order to avoid severe over‐predictions in very light wind speed conditions (as originally suggested by Zimmerman and Thompson (1975) in the HIWAY model) and to take into account the vehicle‐induced turbulence that is likely to dominate the dispersion process in such low ambient wind speed conditions (Ketzel et al , 1999), especially very close to the road and when vehicles are travelling at high speeds (Gronskei, 1988). For the Hamilton site tested in Dirks et al (2002), it was found that provided the leeward and windward cases were separated, there was no significant effect of wind direction on concentration, except for a slight influence in high wind speed conditions when concentrations tend to be low anyway.…”
Section: The Semi‐empirical Modelmentioning
confidence: 99%